2004
DOI: 10.1021/bi049560r
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of Repair of an Abasic Site within DNA Clustered Damage Sites by Mammalian Cell Nuclear Extracts

Abstract: Ionizing radiation induces clustered DNA damage sites which have been shown to challenge the repair mechanism(s) of the cell. Evidence demonstrating that base excision repair is compromised during the repair of an abasic (AP) site present within a clustered damage site is presented. Simple bistranded clustered damage sites, comprised of either an AP-site and 8-oxoG or two AP-sites, one or five bases 3' or 5' to each other, were synthesized in oligonucleotides, and repair was carried out in xrs5 nuclear extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
90
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(102 citation statements)
references
References 34 publications
12
90
0
Order By: Relevance
“…These damaged templates undergo rapid BER incisional activity that subsequently result in increased DSBs [49]. Others have also shown that clustered BER sites on double-stranded DNA can give rise to DSBs by incisional repair activity [59]. Another recent study has demonstrated that MNNG induces replicationindependent DSBs in a dose and MMR-dependent manner, and does not require DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…These damaged templates undergo rapid BER incisional activity that subsequently result in increased DSBs [49]. Others have also shown that clustered BER sites on double-stranded DNA can give rise to DSBs by incisional repair activity [59]. Another recent study has demonstrated that MNNG induces replicationindependent DSBs in a dose and MMR-dependent manner, and does not require DNA replication.…”
Section: Discussionmentioning
confidence: 99%
“…The time course performed on the tandem lesions (3,4) was carried out in the same way as 1 except the 2× enzyme concentration was 200 nM, the 2× DNA solution was 2 nM, and aliquots were removed at 0, 10, 30, 60, 180, 300, 900, 1800, and 3600 s. The time course experiments for the clustered lesion containing duplexes (5,6) were run with a 2× DNA concentration of 2 nM and 2× enzyme concentration of 200 nM. Aliquots were removed at 0, 60, 180, 300, 900, 1800, and 3600 s.…”
Section: Time Course For Nth Excision Of Thymine Glycolmentioning
confidence: 99%
“…Aliquots (1.5 μL) were removed at 0, 10, 30, 60, 180, 300, 900, and 1800 s. Experiments using the clustered lesion containing duplexes (5,6) were carried out in the same way as 2 except aliquots (1.5 μL) were removed at 0, 10, 30, 60, 180, 300, 900, and 1800 s. For experiments with the tandem lesion (3), 2× DNA concentrations used were 50, 100, 150, 250, 500, and 1000 nM, and the reaction time was 3 min. For experiments with the clustered lesion containing duplexes (5,6) the 2× DNA concentrations used were 20, 50, 100, 150, 250, and 400 nM, and the reaction time was 1 min.…”
Section: Time Course For Nfo Incision Of 2-deoxyribonolactone (L) or mentioning
confidence: 99%
“…Whereas both ATM activation and ␥H2AX are correlated with the presence of double-strand breaks (DSBs) in the genome (Abraham, 2001;Pilch et al, 2003), these biochemical events indicate that DSBs occur in response to high-dose MNNG exposure. DSBs generated by alkylators are caused by the simultaneous processing of clustered AP sites on opposite DNA strands (Lomax et al, 2004), and their abundance would be expected to be proportional to initial lesion load. However, given the ATM-independent nature of high-dose MNNG G 2 checkpoint activation, it is unlikely that MNNG-induced DSBs are the dominant lesion that triggers activation of this checkpoint.…”
Section: Mnng-induced Checkpoint Signaling: High-versusmentioning
confidence: 99%